Dust Structure around AGB Star in 60μm and 100 μm IRAS Survey at Latitude 16.10° - Gautam, Arjun Kumar (Himalayan Physics, 2017)
A systematic search in the range of J2000 coordinate system provided by K.W. Shu & Y.J. Kwon (2011) of dust structure in the far infrared (100 μm and 60 μm) IRAS (Infrared Astronomical Satellite) survey was performed using Sky View virtual Observatory (1) so that some interesting isolated cavity structures surrounding the cavity structure were expected. The FITS images downloaded from sky view (1) was processed using software Aladin v 2.5. A cavity like structure (major diameter ∼ 3.57 pc & minor diameter ∼ 1.19 pc) lies in the coordinate of R.A. (J2000) 06h 31m 05s and DEC (J2000) 16d 06m 00s was found at the distance ∼ 310 pc (5). We studied the flux density variation and the temperature variation about major diameter, minor diameter and the distance between minimum temperature and minimum flux within the structure. We observed the variation of the temperature is 20.53 K to 21.42 K, with the offset of about 0.89 K, which shows the cavity is independently evolved. The mass profile of each pixel of the structure was also calculated using these temperature. The Himalayan Physics Vol. 6 & 7, April 2017 (48-53)